Bovine trophoblastic cell differentiation and binucleation involves enhanced endogenous retrovirus element expression - Koshi Katsuo; Suzuki Yasunori; Nakaya Yuki; Imai Kei; Hosoe Misa; Takahashi Toru; Kizaki Keiichiro; Miyazawa Takayuki; Hashizume Kazuyoshi (BMC, 2012)
Abstract Background Endogenous retrovirus (ERV) envelope (env) genes are involved in the differentiation of trophoblastic cells in humans and mice. However, there is limited information about their roles in ruminant trophoblastic cells. Thus, we attempted to explore the possible roles of ERV elements in the binucleation of bovine trophoblastic cells using in vitro bovine trophoblastic (BT) cell lines. Methods In this study, blastocysts and elongated embryos were obtained from Japanese Black cows, and endometrial and fetal membrane tissues were collected from day 17 to 37 of gestation. The gene expression levels of four ERV elements, bERVE (bovine endogenous retrovirus envelope element-like transcript) -A, bERVE-B, BERV (bovine endogenous retrovirus) -K1 env, and BERV-K2 env, were analyzed in the fetal and endometrial tissue and cultured BT cell lines using quantitative RT-PCR. On-Matrigel gel and on-collagen gel culturing were used to induce binucleate cell (BNC) formation in the BT cell lines. How the culture conditions affected the expression of BNC-specific genes and ERV elements was examined by quantitative RT-PCR and immunocytochemistry. Results bERVE-A, bERVE-B, BERV-K1 env, and BERV-K2 env were expressed in almost all BT cell lines; however, only bERVE-A and BERV-K1 env were detected in trophoblastic tissues during the peri-implantation period. In the on-Matrigel cultures, the expression levels of BNC-specific genes and molecules were enhanced in the BT cells. The expression levels of bERVE-A and BERV-K1 env were also increased in the BT cells during on-Matrigel culturing. The BT cell expression levels of these ERV elements were consistent with those of BNC-specific genes during on-Matrigel culturing (P < 0.01). Conclusions These results suggest that bERVE-A and BERV-K1 env are involved in the expression of BNC-specific genes and the progression of bovine trophoblastic cell binucleation, as their expression levels increased during periods of increased BNC-specific molecule expression, which is strongly suggestive of the development of BNC from mononucleate trophoblastic cells. The on-Matrigel culture system is a convenient in vitro tool for studying bovine trophoblastic cell lineages.